Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1103/physreva.53.4127
|View full text |Cite
|
Sign up to set email alerts
|

Electron affinity of Li: A state-selective measurement

Abstract: We have investigated the threshold of photodetachment of Li^- leading to the formation of the residual Li atom in the $2p ^2P$ state. The excited residual atom was selectively photoionized via an intermediate Rydberg state and the resulting Li^+ ion was detected. A collinear laser-ion beam geometry enabled both high resolution and sensitivity to be attained. We have demonstrated the potential of this state selective photodetachment spectroscopic method by improving the accuracy of Li electron affinity measurem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 20 publications
7
43
0
Order By: Relevance
“…To obtain the final EA value we added the QED corrections calculated by Pachucki and Komasa to our result. The value of EA we got agrees well with the most recent experimental result of Haeffler et al 25 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To obtain the final EA value we added the QED corrections calculated by Pachucki and Komasa to our result. The value of EA we got agrees well with the most recent experimental result of Haeffler et al 25 …”
Section: Discussionsupporting
confidence: 81%
“…With those corrections, our EA of Li equals to 4984.9867 cm −1 . This result agrees very well with the EA 25 Finally, we found that it interesting to examine how the EA converges with the number of functions in the basis set. The pertinent information is presented in Table III.…”
Section: Resultssupporting
confidence: 74%
“…All the other reference values a−g are experimental data [36][37][38][39][40][41]. b References [36,37].…”
Section: Test Calculationsmentioning
confidence: 99%
“…EC in Table I means the value calculated by the EOM coupled cluster singles and doubles (EOM-CCSD) with aug-cc-pV5Z basis set using Gaussian 09 [35]. References [36][37][38][39][40][41][42][43][44][45] are all experimental data. We find good agreements between the EQP energies of the forward (→) electron absorption process and the backward (←) electron release process.…”
Section: Test Calculationsmentioning
confidence: 99%
“…It was then suggested to attempt more precise experiments on other negative ions, with S − as a possible candidate, or to investigate "few-electron" systems, like Li − , for which more accurate calculations could be performed. In this line, a new determination of the Li electron affinity has been reported by Haeffler et al [13] using a state selective photodetachment spectroscopic method but the measurements were unfortunately limited to the 7 Li isotope, shedding no light on the isotope shift in the electron affinity. A satisfactory agreement between theory and observation was found for the isotope shift in the oxygen electron affinity.…”
Section: Introductionmentioning
confidence: 99%